The Philippines’ Anti-Drug Campaign: Building a Dataset of Publicly-Available Information on Killings Associated With the Anti-Drug Campaign - David, Clarissa C (Archīum Ateneo, 2018)
This study assembles the first national victim-level dataset of drug-related killings during the Philippine government’s antidrug campaign under President Rodrigo Duterte. The dataset covers information on 5,021 people killed from May 10, 2016 to September 29, 2017. Based on the data culled mostly from media reports, we identified who were being killed, where, how and why. Over half of the killings were due to police operations, and the rest were killed in so-called “vigilante-style” killings. Those who were killed were mostly low-level drug suspects. Forty percent of the killings were in Metro Manila mostly in Manila, Quezon City, and Caloocan. High death tolls were also observed in Bulacan and Cebu. Killings commonly occurred on the streets or alleys and in or around private homes. The study mainly relies on media sources which is a limitation that we hope to address by expanding the scope of the project.